G30S, sejarah yang digelapkan : tangan berdarah CIA dan rejim Suharto - Harsutejo, 1937- (Jakarta : Hasta Mitra, 2003)
Position of CIA and Soeharto in the Gerakan 30 September 1965, an abortive coup by Indonesian Communist Party.
"Agustus 2003."
Includes bibliographical references (p. [376]-382).
Keywords: United States. -- Central Intelligence Agency -- Influence; United States -- Foreign relations -- Indonesia; Indonesia -- Politics and government -- 1966-1998.; Indonesia -- Foreign relations -- United States; Indonesia -- History -- Coup d'état, 1965.